ECOLOGICAL INTELLIGENCE ON NOVEL SI ANAK PINTAR BY TERE LIYE - Sigit Arif Bowo (Universitas Negeri Makassar, 2020)
This study aims to reveal the form of ecological intelligence in the novel Si AnakPintar (SAP) by TereLiye. This research is in the form of descriptive qualitative. Data collection techniques using the technique of reading and taking notes. Theory triangulation is used to validate data. Content analysis is used as an interactive analysis technique. The results of the analysis show that the forms of ecological intelligence contained in the SAP novel are (1) identifying ecosystem components; (2) understanding the function of ecosystem components; (3) understanding the natural and environmental management system; (4) understanding environmental values; (5) showing concern for environmental damage; (6) adapting the environment; (7) solving problems from environmental effects; (8) managing natural resources; and (9) using the environment positively.